An Effort For Formul Justice Criminal Law Enforcement - Hadi Supriyanto; Amrun Kahar; Mashendra Mashendra; Edy Nurcahyo (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
In criminal law enforcement, legally formally it will lead to administrative issues. Where in the exercise of power related to examination matters at the level of the police, prosecutor's office to the judiciary, it must be able to provide certainty that there is no abuse of power. Not infrequently in a criminal incident, many suspects are involved in it and other actions. The contribution of everyone who commits an act in the same event must be rewarded with appropriate sanctions and may not exceed what has been determined in the laws and regulations (lex scripta). Therefore, in the prosecution process, the prosecutor is obliged to understand the construction of a criminal event, so that each perpetrator of the crime gets a reward for their respective contributions. Separation of case files legally has been regulated in article 142 of the Criminal Procedure Code. known as splitsing or a split trial. Doctrinal research using the statue approach was carried out to answer the normative question whether this splitsing could cause a violation ofOn the other hand, the principle of non-self-incrimination can positive law enforcement be able to achieve justice in law